Hip-directed walking-in-place using a single depth camera. Issue 105 (September 2017) - Bruno, Luís; Sousa, Maurício; Ferreira, Alfredo; Pereira, João Madeiras; Jorge, Joaquim
Abstract: Walking-in-place (WIP) is a locomotion technique that allows users to travel in virtual environments (VEs) without significantly changing their physical position on the floor. Hip-directed steering(HDS) is a novel physical technique for controlling direction changes in virtual travel using hip movements. We present an WIP-based navigation approach for controlling locomotion in VEs that combines the speed and direction in a scenario similar to a domestic setup in which people interact with a flat screen. Their physical motion data are captured by one depth camera properly aligned with the screen and oriented toward the user. We approach the characteristically noisy data generated by depth cameras via a user study to determine both the range of values and their robustness from the motion data associated with the joints relevant to WIP speed(knee, ankle and foot) and HDS (spine, hip and shoulder) to derive a reliable technique. Our WIP speed method is supported in a simple vocabulary of five different footstep types. Experimental results show that both the knee and hip provide the most robust data. We evaluated our techniques via usability tests exercising common locomotion tasks. The results show that users liked both the speed control and comfort afforded by our speed method. Regarding HDS, users reported that the angular-based method allowed them to travel faster and was both more controllable and easier to learn than the time-based method. Our work shows that a single depth camera can be used to combine locomotion and direction control in a simple and affordable setup. Abstract : Graphical abstract: Abstract : Highlights: An approach to locomotion in VR combining Walking-in-place (WIP) and Hip-directed steering (HDS) using only one depth camera. User study to determine values and robustness of lower limbs and torso joints showed that knee and hip provide the best results. User tests with common locomotion tasks in VEs show that users liked both speed control and comfort by WIP method. Tested Two alternative HDS methods to steer WIP locomotion: angular-based (AM) and time-based (TM). AM allowed users to travel faster and was easier to learn than TM.